Report on Prices and Wages by the Senate Committee - W. J. A. (Quarterly Journal of Economics, 1893)
Journal Article Report on Prices and Wages by the Senate Committee Get access W. J. A. W. J. A. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 8, Issue 1, October 1893, Pages 104–108, https://doi.org/10.1093/qje/8.1.104 Published: 01 October 1893